The Frequency and Histological Type of Oral and Maxillofacial Malignancies Presenting at Tertiary Care Hospital - Sarfraz Ali; Jehan Alam; Ruqaya Shah; Ahmad Sohail (Medical Journal of South Punjab, 2025)
Objective: to determine the frequency of common types of oral and maxillofacial malignancies in patients presenting with malignant tumors at tertiary care hospital.Methodology: The study employed a descriptive cross-sectional design and was conducted in the Department of Oral and Maxillofacial Surgery at Jinnah Postgraduate Medical Centre, Karachi, from November 2023 to May 2024. The study focused on the histological types of oral and maxillofacial malignancies, which were classified based on cellular and tissue characteristics identified through microscopic examination. Data were collected using a customized proforma, recording biographical details and study variables such as frequency and histological typing based on histopathology reports.Results: The study included 175 patients, majority of the patients 85.1% aged >40 years. Tobacco use was prevalent among the study patients i.e. smoking 35.4%, pan 27.4%, and ghutka 22.9%. It was seen that squamous cell carcinoma 54.9% dominated carcinomas, followed by mucoepidermoid 24.6% and adenoid cystic 13.7%. Among sarcomas, Burkitt’s lymphoma 58.3% was most frequent, followed by osteosarcoma 34.9%.Conclusion: This study highlights the predominance of squamous cell carcinoma among carcinomas and Burkitt’s lymphoma among sarcomas, with significant age-related differences in sarcoma subtypes. The high prevalence of tobacco use underscores the need for targeted public health interventions to reduce modifiable cancer risk factors.